ANALYSIS OF EXERGY PARAMETERS OF BIOGAS POWER PLANT - Denysova A.E.; Ngo Minh Hieu (Problems of the Regional Energetics, 2014)
The techniques of an exergy analysis concerning various circuits of biogas units, which allows replacing traditional energy resources and improving environmental conditions, has been presented. The heat schemes of biogas units were proposed, and analysis of their effectiveness was made. The comparison of different cycle parameters of various biogas units (i.e. a combustion turbine unit, a combined cycle gas turbine unit with gas discharges into the boiler and a combined cycle gas turbine with a high-temperature vapor generator and a reheating stage) was made, and the comparison of their exergy characteristics was carried out. The results of exergy analysis had demonstrated that the cycle of biogas CCGT (combined cycle gas turbine) with a reheating stage and using a high-pressure steam generator is the most effective, that can be explained by the fact that the thermal energy proportions of combustion products, accounting for the steam cycle and the gas cycle are approximately equal, comparing to conventional combined cycle gas turbine units.